The effects of melatonin and pentoxiphylline on L-arginine induced acute pancreatitis - Bülbüller, Nurullah; Do?ru, Osman; Umaç, Hayati; Gürsu, Ferit; Akpolat, Nusret (My University, 2005)
BACKGROUND: It has been showed that free oxygen radicals and cytokines contribute to tissue damage and impairment of pancreatic microcirculation in acute pancreatitis. In this study, the effects of melatonin and pentoxiphylline were investigated in rabbits with L-arginine induced acute pancreatitis. METHODS: Rabbits were divided into 5 groups (n=10). Any procedure was not applied for the control group (G1). Acute pancreatitis was induced in one group (G2). Melatonin (G3), pentoxiphylline (G4) and melatonin + pentoxiphylline (G5) were given to other groups after induction of acute pancreatitis. Plasma levels of MDA, amylase, LDH, SGOT, IL-6 and TNF-? were measured at 0., 6., 12., 24. and 48. hours and pancreatic tissue was assessed histopathologically. RESULTS: Melatonin significantly reduced amylase activities at 6., 12., 24., and 48. hours (p<0.025), and all biochemical parameters, (excl. MDA) and edema and necrosis of acinar cells after 48 hours. Although pentoxiphylline reduced abnormally increased parameters in acute pancreatitis (significant for SGOT at 6.,12.,24. and IL-6 at 12.,48. hours), it did not normalized pancreatic abnormalities. CONCLUSION: Melatonin in contrast to pentoxiphylline significantly improved biochemical and histopathological abnormalities due to its powerful antioxidant and free oxygen scavenger properties in acute pancreatitis, and could be used for patients with pancreatitis.
L-arjinin ile oluşturulan akut pankreatit üzerine melatonin ve pentoksifilinin etkileri
Keywords: Acute pancreatitis; L-arginine; Melatonin; Pentoxiphylline